Regional aspects of the chemical industry development in Kazakhstan - OKAY, GÜÇLÜ (My University, 2021)
he chemical complex is the basic segment of Kazakhstan's industry, which lays the foundations for its long-term and stable development and has a significant impact on structural changes in the economy, which have a significant macroeconomic impact and affect the level of national competitiveness and the growth rate of the economy as a whole. The article considers the main trends in the development of the chemical industry in the regions of Kazakhstan. Special attention is paid to the development of the chemical industry in the south of Kazakhstan -in the Turkestan region and the city of Shymkent. A feature of the development of the industry in the dynamics of recent years has been an increase in the scale of activity. At the same time, there is a decrease in demand for products in the domestic market, primarily from high-tech industries, as well as a decrease in the growth rate of production and financial sustainability of chemical enterprises. In the course of the study, the authors identified the problems of industry development in the region associated with a high degree of depreciation of the main capital of the industry, low competitiveness of domestic chemical products, the lack of a developed system for attracting advanced technologies in the chemical industry, etc. Based on the analysis, prospects and strategies for the development of the chemical industry in south Kazakhstan were determined